Pengaruh Kecerdasan Emosi, Prasangka, dan Kualitas Pertemanan terhadap Sikap Toleransi Siswa pada Sekolah Berbasis Agama - Ghorbal, Shofiq; Lestari, Sri (Jurnal Penelitian Pendidikan Islam, 2021)
Tolerance has an important role to maintain harmony and peace in society. However, the reality shows that tolerance among youth has not developed as expected. The purpose of this study was to determine whether or not there is a significant influence between emotional intelligence, prejudice and friendship quality on the tolerance attitude of students in religion-based schools. This study uses a quantitative approach with a survey method. A total of 406 students from faith-based schools participated in this study by filling out the tolerance scale, emotional intelligence scale, prejudice scale and friendship quality scale. The research data were analyzed using regression analysis techniques. The results showed that emotional intelligence, prejudice, and the quality of students' friendships had an effect on students' tolerance in religion-based schools. Friendship quality was the strongest predictor of student tolerance, followed by emotional intelligence and prejudice. The world of education needs to develop the quality of friendship as one of the factors that contribute to the development of tolerance in students.